The Effect of Pre-operative Psychological Interventions on Psychological, Physiological, and Immunological Indices in Oncology Patients: A Scoping Review - Hanalis-Miller, Tsipi; Nudelman, Gabriel; Ben-Eliyahu, Shamgar; Jacoby, Rebecca (Frontiers in Psychology, 2022)
Introduction The stressful pre-operative period exerts a profound impact on psychological, physiological and immunological outcomes. Oncological surgeries, in particular, elicit significantly higher stress responses than most other surgeries. Managing these responses through psychological interventions may improve long-term outcomes. The purpose of the current research was to review studies that have explored pre-operative psychological interventions in cancer patients in order to map the types of current interventions and provide an initial assessment of whether these interventions improved psychological, physiological, and/or immunological indices as well as long-term cancer outcomes. Methods A systematic literature search for studies that included pre-operative psychological interventions in oncology patients was conducted, using the databases PubMed and Web of Science. Inclusion criteria included studies pertaining to oncological surgery in adults, study designs that included a clearly defined pre-operative psychological intervention and control group. Results We found 44 studies, each using one of the following interventions: psychoeducation, cognitive interventions, relaxation techniques, integrated approaches. All the studies reported improved immediate post-operative psychological, physiological, and/or immunological outcomes. Only a few studies addressed long-term cancer outcomes, and only one reported improved survival. Conclusions Research on pre-operative interventions with cancer patients is missing systematic methods. Studies provide varying results, which makes it difficult to compare them and reach reliable conclusions. There is considerable heterogeneity in the literature regarding the specific intervention used, the timing of intervention, the characteristics of the patients studied and the outcome measures. In order to improve research in this field, including the measurement of long-term outcomes, we suggest some steps that should be taken in further research.